Khurūj sebagai Syarat Pernikahan Jamā’ah Tablīgh Pakapuran Amuntai Kalimantan Selatan - Muhammad Rifqi Hidayat (State Islamic University (UIN) of Sunan Ampel, 2014)
Abstract: This article discusses the term of khuruj as a requirement of applying marriage for Jamaah Tabligh of Pakapuran Amuntai, South Kalimantan. This requirement is due to their belief that khuruj is a powerful tool to increase faith, while faith itself is the most important provision for the life of the world and in the hereafter, including marriage. In addition, the reservation stems from their fear about the inability of their young people in doing khuruj in a long time due to a variety of busy after marriage, as well as a manifestation of the Prophet Muhammad’s suggestion to fill youth with obedience to God. Khurūj, as a condition of marriage in the case of the Jamaah Tabligh’s members, is basically not regulated in Islamic law. Islamic law only requires the prospective groom to pays dowry to bride or do covenant of marriage. Within the perspective of the marriage covenant, it appears that the elements contained in such cases are in line with what is required in the legal basis and the terms of the marriage covenant. Therefore khurūj is not prohibited in Islamic law.